African Honey Bee Information for School Administrators - Michael K. O'Malley; James D. Ellis; Anita S. Neal (EDIS)
ENY-142, a 2-page fact sheet by M. K. O’Malley, J. D. Ellis, and A. S. Neal, provides information about Africanized honey bees (AHB), precautions that can be taken on school grounds, an administrator’s checklist, and additional resources. Published by the UF Department of Entomology and Nematology, December 2007.